Between Ecological Psychology and Enactivism: Is There Resonance? - Ryan, Kevin J.; Gallagher, Shaun (Frontiers in Psychology, 2020)
Ecological psychologists and enactivists agree that the best explanation for a large share of cognition is nonrepresentational in kind. In both ecological psychology and enactivist philosophy, then, the task is to offer an explanans that does not rely on representations. Different theorists within these camps have contrasting notions of what the best kind of nonrepresentational explanation will look like, yet they agree on one central point: instead of focusing solely on factors interior to an agent, an important aspect of cognition is found in the link or coupling between an agent and the external world. This link is fluid, dynamic, and active in a variety of ways, and we do not need to add any internal extra something in the perception-action-cognition process. At the same time, even devout defenders of ecological psychology and enactivism recognize that plenty happens inside an agent during cognition. In particular, no one denies that the brain plays an important role. What, then, is the role of the brain if it’s not in the game of representing the environment? One possible option is to describe the brain as a resonant organ instead of a representational organ. In this paper we consider the history of resonance in more detail. Particular focus will be placed on two different sets of approaches that have developed the concept of resonance: a representational reading of resonance and a nonrepresentational, dynamic account of resonance. We then apply these accounts to a case study on music performance, specifically in the context of standard tonal jazz. From this application, we propose that a nonrepresentational resonance account consistent with both enactivism and ecological psychology is a viable way of explaining jazz performance. We conclude with future considerations on research regarding the brain as a resonant organ.